Life-history traits in the southernmost landlocked population of the fish Galaxias maculatus - Rojo, Javier Hernán; Boy, Claudia Clementina (Polar Biology)
Studying life-history traits is critical to understanding the intraspecific variation among fish populations. In this research, we investigated the age, growth, and sexual maturity of Galaxias maculatus population from Laguna Negra (LN), the southernmost landlocked population of the species, and compared the results obtained with those obtained before for the diadromous population from Arroyo Negro (AN), 1.8 km away from LN. We read otolith growth bands to estimate age structure and calculated the gonadosomatic index to estimate sexual maturity. We found five age classes (0 + to 4 +) in LN; the maximum age was 4.5 years, the maximum documented age for the species, exceeding in 1 year the maximum age found previously for the AN population. Age class 2 + was the most represented throughout the year, and the greater age and length-at-age ratio observed in this landlocked population suggest a slower growth rate than that of AN. We hypothesize that landlocked individuals reach their first sexual maturity 1 year later than their diadromous counterparts. The protracted reproductive season detected in this landlocked population (9 months) may be related to the high size variability within age classes, where some individuals might maximize growth while others might maximize first sexual maturity. Our results suggest higher energetic costs for these basic biological activities in landlocked than diadromous populations from Tierra del Fuego, Argentina. Further studies are necessary to understand the trade-off between growth and sexual maturation in sub-Antarctic G. maculatus populations. Fil: Rojo, Javier Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Boy, Claudia Clementina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina